2023
DOI: 10.1021/acssuschemeng.3c01168
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Multiblock Copolymer Elastomers Derived from Lignin with Tunable Performance toward Strong Adhesives and UV-Shielding Materials

Abstract: With the increasing concern about global environmental issues, reducing the carbon footprint to achieve carbon neutrality has been particularly important. Sustainable multiblock copolymer elastomers (MBCPEs) have received tremendous interest due to their unprecedented performance and huge potential applications. However, complex multistep polymerization and postpolymerization processes are needed to design MBCPEs. In this work, a series of MBCPEs, in which vanillin acrylate (VA) derived from lignin was selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Specifically, L-P(BA 350 - co -GMA 150 ) b -SA could achieve a lap shear strength of 4.083 MPa, approximately three times higher than that of P(BA 350 - co -GMA 150 ) b -SA. While previous studies often reported increased strength but decreased toughness upon adding lignin to systems, 21,28,32,44 it is noteworthy that both strength and toughness were enhanced in our work, underscoring the significant influence of lignin as a copolymer core on mechanical properties. However, the performance of L-P(BA 250 - co -GMA 250 ) b -SA declined, possibly due to excessive crosslinking density leading to increased brittleness in the material.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Specifically, L-P(BA 350 - co -GMA 150 ) b -SA could achieve a lap shear strength of 4.083 MPa, approximately three times higher than that of P(BA 350 - co -GMA 150 ) b -SA. While previous studies often reported increased strength but decreased toughness upon adding lignin to systems, 21,28,32,44 it is noteworthy that both strength and toughness were enhanced in our work, underscoring the significant influence of lignin as a copolymer core on mechanical properties. However, the performance of L-P(BA 250 - co -GMA 250 ) b -SA declined, possibly due to excessive crosslinking density leading to increased brittleness in the material.…”
Section: Resultssupporting
confidence: 59%
“…This phenomenon arises from the introduction of functional groups such as 2-bromo-isobutyryl bromide and carbon disulfide onto THF-L, resulting in covalent bonds with lower energy within the macromolecule. The DTG profiles clearly indicate temperature ranges of weight loss: between 100 °C and 300 °C, corresponding to the degradation of –C–Br, –C–S, and –CS bonds, 44 while the degradation stage observed beyond 300 °C in all three samples is attributed to the degradation of the benzene ring in lignin. 32…”
Section: Resultsmentioning
confidence: 90%
“…The hydroxyl functional group in vanillin often serves as a starting point for chemical transformation, enabling the synthesis of biobased polymers. For example, vanillin can be acrylated to form polymerizable vinyl monomers, which can then be polymerized using controlled radical polymerization techniques such as reversible addition–fragmentation chain transfer (RAFT) or atom transfer radical polymerization (ATRP) to produce functional polymers. Additionally, by further cross-linking through the combination of aldehyde pendent groups of vanillin, biobased resins can be created. While controlled radical polymerization offers many advantages, it also has inherent drawbacks, such as prolonged reaction times, high reaction temperatures, and chain transfer side reactions. In this context, ring-opening metathesis polymerization (ROMP) can serve as an excellent alternative to radical polymerization.…”
Section: Introductionmentioning
confidence: 99%